The influence of unsportsmanlike fouls on basketball teams` performance according to context-related variables - Gómez, M.-A.; Ortega Toro, E.; Furley, P. (International Journal of Sports Physiology and Performance, 2016)
The aim of the current study was to analyze the temporal effects that unsportsmanlike fouls may have on basketball teams` scoring performance under consideration of context-related variables. The authors analyzed 130 unsportsmanlike fouls from 362 elite basketball games (men`s and women`s Olympic Games, European and World Championships). The context-related variables studied were score-line, quality of opposition, timeout situation, minutes remaining, and player status. The data were analyzed with linear-regression models. The results showed that both teams (the team that made the foul and the opponent) had similar positive scoring performances during 1 and 3 ball possessions after the unsportsmanlike foul (short-term effect). However, 5 ball possessions after the foul (midterm effect), the team that made the foul had a scoring disadvantage (-0.96) and the opponent team an advantage (0.78). The context-related variable quality of opposition was significant only during 1 ball possession, with negative effects for the team that made the foul and positive effects for the opponent. The final outcome showed a positive effect for score-line when the unsportsmanlike foul was made (0.96) and for quality of opposition (0.64).